PENDIDIKAN MULTIKULTURAL: KONSEPSIDAN IMPLEMENTASINYA DALAM PEMBELAJARAN - Zubaedi, Zubaedi (Jurnal Cakrawala Pendidikan, 2016)
The multiculturaleducation concept is analtemative solution to reducing racial antagonisms in our·country. Multicultural education is·education that values cultural pluralism or an education model that aims to promote the transformation of the educational process to reflect the ideals of democracy ina pluralistic society and structural· equality within a larger society. This. concept affirms that schools should be oriented toward the cultural enrichment of. all children and recognize cultural diversity as· reality in. Indonesia that should.be preserved and extended. Thus, one of its important goals is to help all students to acquire knowledge, attitudes, and skills needed to .function effectively in a pluralistic democratic society and to interact, negotiate, and comtnunicatewith people from diverse groups in order to create a civic and moral community that works for the common good. There are three essential goals of multiculhrral educat;ion. The first is to enhance sensitivity to and understanding of others, in cluding cultural groups in Indonesia and other nations. The second is.· to enhance the ability to make decisions and take effective actions .based.ona multicultural analysis and synthesis. The third is to enhance understanding of theprocess.ofstereotypmg, a low degree of stereotypical. thinking, and pride inself and· respect for other people